PENDAMPINGAN IMPLEMENTASI PRINSIP KEADILAN DAN MASLAHAT DALAM SKEMA POTONGAN PELUNASAN DINI PEMBIAYAAN MURABAHAH DI PONDOK PESANTREN ARRAHMAN CIDADAP - Syarif Hidayatullah (LPPM STAI Muhammadiyah Probolinggo, 2023)
This research is a comprehensive report on a community service program conducted at the Arrahman Cidadap Islamic Boarding School, Sukabumi. The primary focus of this study is an in-depth analysis and assistance in the implementation of the National Sharia Board-Indonesian Council of Ulama (DSN-MUI) Fatwa Number 153/DSN-MUI/VI/2022 concerning the Early Settlement of Murabahah Financing Debt, which revises the old paradigm of Fatwa Number 23/DSN-MUI/III/2002. This research is motivated by academic and practical concerns regarding the low literacy of the boarding school's financial managers regarding the legal shift from a